Changing land tenure regimes and women's access to secure land for cocoa cultivation in rural Ghana. (September 2022) - Addaney, Michael; Akudugu, Jonas Ayaribilla; Asibey, Michael Osei; Akaateba, Millicent Awialie; Kuusaana, Elias Danyi
Abstract: The global literature on the ownership of, access to and control over land for agricultural activities, specifically for cocoa production, reports on gender discrimination, which affects the productivity and wellbeing of women farmers. Yet, the relationship between changing tenure dynamics and women's access to land is inconclusive and blurred in many sub-Saharan African countries, particularly, Ghana. However, understanding this relationship is important in promoting productivity and improving wellbeing, especially of women across Africa. The paper thus examines the determinants and implications of the changing land tenure regime on women cocoa farmers. Using Dormaa Central Municipality of the Bono Region of Ghana as a case study, household surveys and agency interviews were conducted. From the study, land tenure arrangements in the study communities have transformed from the ownership by the extended family to more individualised ownership through inheritance, gift, or purchase. Even though sharecropping presents a major opportunity for women to improve their land needs, the results indicate gender discrimination under the sharecropping arrangements as landowners prefer men to women. This is because the latter do not have the required resources to undertake commercially beneficial farming. It is also argued that though the emerging land commodification presents an opportunity for women to improve land access for cocoa farming, women are still disadvantaged as they lack the wherewithal to acquire land through purchase. In addition, the existing local customs and practices under the matrilineal system of inheritance are fluid and gendered; thus, hindering women's access to land for cocoa farming. The study calls for continuous engagement and advocacy on land tenure to improve channels of equitable land access for women and subsequently improve their economic fortunes in Ghana's cocoa sector. Highlights: Studies on land ownership and access to cocoa production confirms persistent gender discrimination. Gendered discrimination in agricultural resource access affects productivity and wellbeing. Changing land tenure regime in the cocoa farming sector affects women farmers. Land ownership arrangements have transformed to more individualised ownership. There is a to improve channels of equitable land access for women in Ghana's cocoa sector.